(untitled) (Homoeopathy for All, 2024)
Mother Tincture is the concentrated herbal extract made from raw lant materials (like roots, leaves or flowers) and alcohol and water which serves as a base. It is the foundational substance used in homoeopathy to created diluted remedies.in homoeopathy mother tincture is made by soaking or macerating plant or other sources in alcohol, which extracts the active compounds. This base is extract is then diluted in a series of step to make homoeopathic remedies. Mother tinctures serve as the initial, concentrated form of a remedy from which further dilutions and preparations are made.